THE RELATIONSHIPS BETWEEN SELF-REPORTED HEALTH STATUS AND SUBJECTIVE HEALTH LITERACY AMONG YOUNG ADULTS IN LITHUANIA - Cesnaviciene, Jurate; Ustilaite, Stase; Kalinkeviciene, Ausra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Seeking to successfully act in the 21st century, a person should have a relatively big spectrum of abilities and competences; in other words, s/he should develop literacy in a number of spheres. Health literacy is essential for a person’s daily capability to manage own health and the quality of life, which is dependent on it. It is significant for the social and economic development of the society. The purpose of the research was to identify the relationships between subjective health literacy and self-reported health status among young adults in Lithuania. The methods of the research included the analysis, interpretation and generalisation of scientific literature on the topic of research, as well as anonymous questionnaire survey. Self-reported health status was ascertained by a single WHO recommended question: “How is your health in general?” Subjective health literacy of young adults was measured using an HLS-EU-Q-47 questionnaire. The survey was conducted in 2014. The research sample included 798 young adults. The results showed high correlation between health literacy in the three health relevant areas and general health literacy. Having generalised the research data, it was noted that the young adults with good/very good selfreported health status tend to achieve sufficient or excellent levels of health literacy on health care, disease prevention or health promotion and general health literacy.